Lean Production for Reducing Wastes in Convex Lens Production Process - Tossapol Kiatcharoenpol; Wanchai Rattanapakdee; Sakon Klongboonjit (My University, 2023)
This research aimed to investigate the waste generated during the production of traditional convex lens. The study proposed a method to eliminate such waste by utilizing value stream mapping (VSM) as a tool for data collection and waste identification throughout the entire production process. Through the analysis of data using VSM, three specific types of waste were identified. These included losses resulting from ineffective utilization of the oven machine during the polymerization process, inefficiencies in personnel performance, and inappropriate working procedures. To address these waste issues, the task employed the work study method to optimize machine utilization, develop efficient work processes for personnel, and improve inappropriate procedures to enhance overall efficiency. The ECRS method was utilized to improve the process of waste elimination. The research findings demonstrated substantial reductions in waste within the production process. Specifically, the total throughput time decreased from 661.07 minutes to 480.68 minutes, representing a reduction of 27.29%. Furthermore, the total production lead time decreased from 1.20 days to 0.94 days, indicating a reduction of 21.67%. In terms of personnel, the workforce decreased from 42 employees per shift to 29 employees, reflecting a decrease of 30.95%. Finally, the number of oven machinery units required for all three shifts decreased from 3 ovens to 2 ovens, resulting in a reduction of 33.33%.
Keywords: Value stream mapping; Manufacturing Process and Optimization